2016
DOI: 10.4186/ej.2016.20.2.17
|View full text |Cite
|
Sign up to set email alerts
|

Study of Flow Pattern in Jet Clarifier for Removal of Turbidity by Residence Time Distribution Approach

Abstract: Abstract. This study aims to determine the performance of the jet clarifier for turbidity removal and its mechanisms for proposing the optimal operating conditions and design criteria. The experiment were performed continuously using a pilot scale jet clarifier with the volume of 243 L. Effects of liquid flow rates, types of liquid phase, and sludge blanket heights on turbidity removal efficiency were investigated. Moreover, the residence time distribution (RTD) study was carried out to investigate the flow pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…High-efficiency clarifiers such as Densadeg, Multiflo and Actiglo have been introduced and applied in many water plants in China since 2005 [1][2][3][4][5][6]. In the operation, the flocs were deposited on the bottom plate on the side of the sedimentation tank in a plant.…”
Section: Introductionmentioning
confidence: 99%
“…High-efficiency clarifiers such as Densadeg, Multiflo and Actiglo have been introduced and applied in many water plants in China since 2005 [1][2][3][4][5][6]. In the operation, the flocs were deposited on the bottom plate on the side of the sedimentation tank in a plant.…”
Section: Introductionmentioning
confidence: 99%
“…Jet velocity plays an important role in determining the high pressure and discharge required to achieve fluidization conditions. The role of the jet stream, has even been developed by Ploypailin Romphophak et.al [21] to dispose of water turbidity.…”
Section: Introductionmentioning
confidence: 99%
“…The main available data are generally presented in terms of turbidity removal and their conclusions do not converge on all points. Romphophak et al (2016) studied the effect of flow rate used on the jet clarifier to reduce the turbid synthetic water: it was concluded that efficiency of about 80% can be achieved at the flow rates of 40 -180 L/h (60000 < Gt < 90000). Kumar et al (2009) showed that, for square and circular flocculators (37000 < Gt < 60000), the turbidity removal was maximum when the nozzle was located 50% of the height of the tank and that when the detention time increases the residual turbidity sharply falls.…”
Section: Mixing and Flocculation In Jet Clarifiermentioning
confidence: 99%
“…and the reactor base, and the height of the sludge blanket is 25 cm. for the LSP that is shown in Figure 2.1 (a) (Romphophak, 2013). Nevertheless, the diameter of the truncated cone's base might be another important factor since it might affect the flocculation zone directly has not still evaluated yet; therefore, it would be evaluated to evaluate its effect on flocculation and fill the research gap.…”
Section: Efficiencymentioning
confidence: 99%
See 1 more Smart Citation